Removal of extensive maxillary dentigerous cyst via a Caldwell-Luc procedure - Asha'ari, Zamzil Amin; Amran, M; Khairudin, A (Universiti Sains Malaysia, 2008)
A case of a large dentigerous cyst associated with canine tooth in the maxillary antrum is presented. This case is of interest because of its extensiveness and the presence of an ectopic tooth in the roof of the maxillary sinus. Theoretical aspects of canine impaction and cyst formation are reviewed. The management of a jaw cyst, in particular, the still popular Caldwell- Luc procedure is discussed.